Bilan socio-économique des pertes pour cause d’inondation de la rivière Saint-François - Viau, Robert (Assurances)

(untitled) (HEC Montréal, 1987)
We are once again pleased to present an interesting article by our collaborator Mr. Robert Viau. lt should be noted that the author takes responsibility for the conclusions drawn in his study.